Is there a duration-characteristic relationship for trypsin exposure on tendon? A study on anterior cruciate ligament reconstruction in a rabbit model - Ma, Rongxing; Gao, Xiaokang; Jin, Yangyang; Wang, Xiaolong; Li, Ruifeng; Qiao, Ruiqi; Wang, Xinliang; Liu, Dayong; Xie, Zhitao; Wang, Limin; Zhang, Jingyu; Xu, Weiguo; et al. (Frontiers in Medicine, 2024)
Background: Decellularized allograft tendons are highly regarded for their accessibility and reduced risk of immune rejection, making them a promising choice for grafting due to their favorable characteristics. However, effectively integrating reconstructed tendons with host bone remains a significant clinical challenge.Purpose: This study aims to investigate the relationship between the duration of tendon exposure to trypsin and its impact on tendon biomechanical properties and healing capacity.Methods: Morphological assessments and biochemical quantifications were conducted. Allograft tendons underwent heterotopic transplantation into the anterior cruciate ligament (ACL), with specimens harvested six weeks postoperatively for comparative analysis of cell adhesion strength and mechanical performance. Duration-response curves were constructed using maximum stress and cell adhesion quantity as primary indicators.The trypsin treatment enhances cell adhesion on the tendon surface. Adhesive rates, control vs experimental groups (3.10±0.56% vs 4.59±1.51%, 5.36±1.24%, 6.12±1.98%, and 8.27±2.34%, F = 6.755, P = 0.001). However, increasing treatment duration leads to a decline in mechanical properties. The ultimate load (N), control vs experimental groups (103.30±10.51 vs